Ruminal degradability of black sorghum (Sorghum almum) fodder fiber in different growth stages. - Boschini, Carlos (2006)
The purpose of this study was to determine the ruminal degradability of dry material of black sorghum fodder, cultivated in the highlands of Costa Rica. Samples were taken at different growth periods of the plant. The study was conducted at the Alfredo Volio Mata Experimental Station of the University of Costa Rica. The crop was planted with 18 kg/ha of seed (88% pure germinal seed), distributed continuously in furrows separated by 70 cm. It was fertilized with 244 kg of 10-30-10 (N2, P2O5, K2O) and after 6 weeks, 45.5 kg/ha of nitrogen was applied. The first sample was taken after 24 days and then every 14 days for a total of 150 days. The potential degradability of the dry material was determined for the leaves, stems and panicles. The potential degradability of the whole plant diminished from 90% to 75% as the plant grew during the first 94 days. In the stem, the soluble part diminished from 32% to 23%, while that of the leaves was reduced from 30% to 16%. The degradable portion in the stem was reduced from 57% to 46% as the plant developed, while that of the leaves increased from 56% to 69%. The degradation rate in the stems was 4.7%/h after 52 days and in the leaves it was 8.6%/h. Between the 66th and the 94th days it was 2.6 %/h in the stems. In the leaves it was 5.4%/h, 3.3%/h and 3.8%/h on the 66 th, 80 th and 94 th day, respectively.